Food in unpublished economic texts from the ancient akkadian period - alwash, Huda hadi (Al-Adab Journal, 2020)
The food is called the Sumerians and the akkadian (akalu) , he has an indispensable need in his daily life ,as the real product of energy that is used in human nutrition ,on the basis of which civilization were built. Where man realized that there is an eternal truth since ancient times , his survival in nature depends on two things :food and reproduction ,without food ,a person cannot live ,without reproduction , his fate will lead to annihilation and demise